Predictors associated with a range of motion of shoulder rotation in competitive high school water polo players: a cross-sectional study - Amanda Gomes de Assis Couto; Júlia Gonzalez Fayão; Felipe de Souza Serenza; Anamaria Siriani de Oliveira (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: To investigate the factors associated with shoulder rotational range of motion and its correlation with the self-reported function scale and functional assessment of the shoulder (closed kinetic chain upper extremity stability, peak torque of shoulder rotators, glenohumeral internal rotation deficit - GIRD, and pectoralis minor length index) in competitive water polo players. Methods: Thirty-four competitive water polo players (age: 15 +/- 1.6 years) participated in this study. The shoulder rotational range of motion, closed kinetic chain upper extremity stability, pectoralis minor length index, isokinetic torque of shoulder internal and external rotations, and self-reported upper limb function were assessed. The Pearson correlation coefficient was used to test the linear correlation before the multiple linear regressions, that were used to predict the variables associated with the external rotation and internal rotation range of motion ratio (ER/IR ratio) of the throwing limb. Results: A significant association was identified between the throwing limb ER/IR ratio and GIRD, and this observation allows us to infer that GIRD was responsible for 18.4% (p=0.01) of the variation. No associations between ER/IR ratio and the variables closed kinetic chain upper extremity stability, peak torque of shoulder internal rotation, and pectoralis minor length index were identified. Conclusion: Anatomical GIRD was the only factor associated with the ER/IR ratio in asymptomatic competitive water polo players from high school, indicating the beginning of the typical adaptations to increase performance without significantly altering the self-perception and functionality of their upper limbs.